China: Challenges and Opportunities in the Trade and Investment Relationship with Mexico - Hernández Zermeño, María Cristina; Enciso Manzo, José Luis (Revista Mexicana de Política Exterior, 2024)
In this article, the authors propose an answer to the question of whether Mexico’s relationship with China represents a challenge or an opportunity, and what actions our country could take to mitigate risks or enhance possible benefits of greater commercial interaction with the Asian giant. To do so, they present a general overview of the commercial relationship between the two countries and ask if nearshoring is really an area of opportunity to attract Chinese investment to Mexico.